Enhanced electrokinetic properties and antimicrobial activities of biodegradable chitosan/organo-bentonite composites - Cabuk M.; Alan, Yusuf; Unal H.I. (Elsevier Ltd, 2017)
In this study, chitosan (CS), Na+-bentonite (Na+-BNT) and chitosan/organo-bentonite (CS/O-BNT) biodegradable composites having three different compositions were investigated. Electrokinetic measurements were examined in aqueous medium by taking the effects pH, electrolytes (NaCl and BaCl2), surfactants (CTAB and SDS), and temperature into account. It was noticed that the initial ?-potential of Na+-BNT shifted from negative (? = ?35 mV) to positive region (? = +13 mV) with increasing polycationic CS content in the composite structure as aimed. Divalent 2:1 electrolyte (BaCl2) caused to shift the ?-potentials of all the dispersions to more positive regions. While the most negative effect on ?-potential of the composites was reached with SDS, which reduced the value of ?-potential to ?39 mV for CS(1)/O-BNT composite, the most positive effect was monitored with CTAB (? = +40 mV) for CS(3)/O-BNT composite. Further, the composites were tested against various bacterial (Gram-positive and Gram-negative) and fungal microorganisms at various concentrations and results obtained were compared with the reference antibiotics and fungicide. According to inhibition zone values accomplished, antibacterial and antifungal activities of the CS/O-BNT composites are increased with increasing CS content as proportional with their positive ?-potential values. © 2017 Elsevier Ltd
PubMed ID: 28189248
Keywords: Antimicrobial activity; Chitosan; Fungicide; Organo-bentonite; SEM-EDS; Zeta potential